Gender Differences in Throwing Revisited: Sensorimotor Coordination in a Virtual Ball Aiming Task - Crozier, Dena; Zhang, Zhaoran; Park, Se-Woong; Sternad, Dagmar (Frontiers in Human Neuroscience, 2019)
Numerous studies have demonstrated that boys throw balls faster, farther and more accurately than girls. This is largely due to well-known anatomical and muscle physiological differences that play a central role in overarm throwing. With the objective to understand the potential contribution of coordinative aspects in this gender difference, this large cross-sectional study examined a simplified forearm throw that eliminated the physical advantages of male individuals. As hypothesized, the gender disparity disappeared, but only in the age groups younger than 20 years. Two fine-grained spatiotemporal metrics displayed a similar age-dependent gender disparity. As throwing experience did not explain this age-dependency, the results are discussed in the context of spatial abilities and video game experience, both more pronounced in males. In contrast, a measure of intrinsic rhythmicity developed over successive throws did not reveal any gender differences, speaking to the fundamental tendency in humans to fall into rhythmic patterns. This computational study was performed in a large cohort in the context of an outreach activity, demonstrating that robust quantitative measures can also be obtained in less controlled environments. The findings also alert that motor neuroscience may need to pay more attention to gender differences.